Sistema de apoio a programação de intervenções no sistema elétrico de transmissão baseado em realidade virtual - Prado, Paulo Roberto Moreira do (2016)
Maintenance in the Electric Power Transmission System must be planned in the aspects of the maintenance team, or field staff, and from the point of view of system operation as well. Nowadays, the operating actions occur remotely, usually through Operation Centers. The field teams address in carrying out their tasks with the real system, with the equipment physically installed in a substation. On the other hand, operating teams in the Operation Centre's typically treat the power grid through the single-line representation of its devices and components. The goal of this research is to evaluate the use of a 3D representation of the substations supporting the planning of maintenance. The 3D system will be used by the field teams and by the teams in the Operation Centre and will be used jointly approaching the perceptions of these teams about the electrical system to be worked.